1991
DOI: 10.1161/01.cir.83.3.974
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of regional myocardial blood flow with multiple colored microspheres.

Abstract: BACKGROUND The use of radioactive microspheres (RM) for the measurement of regional myocardial blood flow (RMBF) is limited and inaccessible to many investigators due to radiation safety concerns and radioactive waste disposal problems. Therefore, a new method for the measurement of RMBF using colored microspheres (CM) was developed. METHODS AND RESULTS Polystyrene spheres (diameter, 15 +/- 0.1 [SD] micron; density, 1.09 g/ml) were dyed with one of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(170 citation statements)
references
References 13 publications
4
165
1
Order By: Relevance
“…Graded ischaemia [19], ischaemic preconditioning [20] and the coronary microcirculation [21] have all been studied in different porcine models. In vivo imaging in pig models has previously been used to study coronary blood-flow using coloured microspheres [22], microvascular function using computer tomography (CT) [23], and to validate novel perfusion tracers for positron emission tomography (PET) [24]. Other applications include validation of MR-guided real time coronary catheterization or percutaneous transluminal balloon angioplasty in aortic coarctation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Graded ischaemia [19], ischaemic preconditioning [20] and the coronary microcirculation [21] have all been studied in different porcine models. In vivo imaging in pig models has previously been used to study coronary blood-flow using coloured microspheres [22], microvascular function using computer tomography (CT) [23], and to validate novel perfusion tracers for positron emission tomography (PET) [24]. Other applications include validation of MR-guided real time coronary catheterization or percutaneous transluminal balloon angioplasty in aortic coarctation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A number of non-radioactive alternatives have been proposed, including coloured microspheres (Hale et al 1988;Kowallik et al 1991;Hakkinen et al 1995;Degens et al 1996) and X-ray fluorescent microspheres (Morita et al 1990;Mori et al 1992), although they have been shown to have some disadvantages. For example, coloured microspheres may underestimate RBF, since they have limited resolution due to significant spectral overlap among different colours, while data variance is high as a result of the low signal intensity (Hale et al 1988;Kowallik et al 1991;Prinzen & Glenny, 1994;Degens et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, coloured microspheres may underestimate RBF, since they have limited resolution due to significant spectral overlap among different colours, while data variance is high as a result of the low signal intensity (Hale et al 1988;Kowallik et al 1991;Prinzen & Glenny, 1994;Degens et al 1996). The X-ray fluorescent microspheres technique uses a measurement system that is expensive and not in common use (Prinzen & Glenny, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When appropriately sized microspheres are used, RBF is proportional to the number of spheres trapped in the region of tissue of interest [21,22]. Acute, tissue specific studies in small animal models suggest that 15 μm-diameter microspheres do not significantly alter RBF or vascular tone [21,23].…”
Section: Microsphere Protocolsmentioning
confidence: 99%